Sociodrama in Imrpoving Self-Adjustment - Putri, Nenden Sulistyanti; Astuti, Budi (Universitas Mercu Buana Yogyakarta, 2021)
Abstract: This article was written to see how effective it is to improve self-adjustment using group guidance services with sociodrama techniques for grade VIII students at SMP Negeri 1 Yogyakarta. This study used aresearch method quasi-experimental design and used amodel non-equivalent control grouppretest and posttest design by comparing the results of 2 groups of research, namely the experimental group which was given services in the form of sociodrama and the control group which was only given the task for independent discussion. Students involved in this service, respectively, the experimental group and the control group amounted to 9 students. Each meeting uses different materials that are used from the aspects contained in the scale grid that is used to be distributed to students to determine the results of the pretest and posttest. The data analysis technique used in this research was thetest Wilcoxon to determine the effect of sociodrama in service delivery. The results of the research that have been carried out indicate an increase in self-adjustment after being given treatment in the form of sociodrama as seen from the comparison of theresults pretest of 74.11 and posttest of 99.78. It can be concluded that there is a significant increase in value and sociodrama has an effect on increasing student adjustment.Keywords: Sociodrama, Self-Adjustment, Students Â Abstrak: Artikel ini ditulis bertujuan untuk melihat seberapa efektifnya peningkatan penyesuaian diri menggunakan layanan bimbingan kelompok dengan teknik sosiodrama pada siswa kelas VIII di SMP Negeri 1 Yogyakarta. Penelitian ini menggunakan metode penelitian quasi eksperimental design dan menggunakan model non-equivalent control groups pretest dan posttestÂ design dengan membandingkan hasil penelitian 2 kelompok yaitu kelompok eksperimen yang diberikan layanan berupa sosiodrama dan kelompok kontrol yang hanya diberikan tugas untuk diskusi secara mandiri. Siswa yang terlibat dalam layanan ini masing-masing kelompok eksperimen maupun kelompok kontrol berjumlah 9 siswa. Setiap pertemuan menggunakan materi yang berbeda yang digunakan dari aspek yang terdapat dalam kisi-kisi skala yang digunakan untuk dibagikan kepada siswa-siswa untuk menentukan hasil pretest dan posttest. Teknik analisis data penelitian ini menggunakan uji Wilcoxon untuk mengetahui pengaruh sosiodrama dalam pemberian layanan. Hasil penelitian yang sudah dilakukan menunjukkan adanya peningkatan penyesuaian diri setelah diberikan treatment berupa sosiodrama yang dilihat dari perbandingan hasil pretest sebesar 74,11 dan posttest sebesar 99,78. Dapat disimpulkan bahwa adanya kenaikan nilai secara signifikan dan sosiodrama memiliki pengaruh terhadap peningkatan penyesuaian diri siswa.Kata Kunci: Sosiodrama, Penyesuaian Diri, SiswaÂ